"Girls Can't Play Ball": Feminist Counseling Using A League of Their Own. Issue 1 (2nd January 2017) - Brown, Colton; Hammer, Tonya; Currin, Joseph M.
ABSTRACT: This commentary reviews A League of Their Own, a film that provides a fictional account of the lives of women who played in the first year of the All-American Girls' Baseball League. Set during World War II-era America, the film offers a look into the gendered lives of women seeking careers in traditionally masculine fields. The authors review the movie from a feminist media lens, with specific emphasis on how the two main characters, Dottie and Kit, ascribe to and defy gender stereotypes and gain voice and agency. Specific implications are pulled from the analysis to be used in the context of counseling women, including empowerment of female clients and establishing career identity.